(untitled) (Agroindustrial Science, 2022)
In the hydration of grains, it is sought to develop novel approaches to reduce the kinetic time and obtain better properties by taking advantage of the time to incorporate nutrients. This review seeks to publicize the potential of ultrasound in seed hydration and its effect on the properties of starches. It has been found that ultrasound accelerates the hydration and germination process in the grains without altering the properties of starch, and the extraction of alkaloids, it reduces the cooking time with ferrous sulfate, but at high temperatures, it hinders the effect of ultrasound. Adding sodium bicarbonate accelerates the softening kinetics, but slows down the hydration process. In quality parameters, zoning and thermal treatments cause an increase in the size of the granules and improve the rate of incorporation of water, obtaining better characteristics suitable for use in industry. Future studies could use other nutrients or salt solutions in the hydration process such as sodium bisulfate (NaHSO4), sodium bisulfite (NaHSO3) and ferrous fumarate (C4H2FeO4), as well as investigate other grains such as chickpeas, lentils and popping beans and Andean grains.